2020
DOI: 10.1590/1980-0037.2020v22e58196
|View full text |Cite
|
Sign up to set email alerts
|

The range of motion of the back squat exercise affects absolute volume load without changing the rating of perceived exertion

Abstract: The range of motion (ROM) may affect the external maximal load during back squat (BS) exercise. The correct ROM manipulation can be useful as an exercise load manipulation strategy, changing the volume load during a resistance training session. The aim of this study was to evaluate the acute effects of ROM on relative load, absolute load and the rating of perceived exertion (RPE) during partial and full BS exercise with adjusted loads. Fifteen male individuals (age: 26.5±4.5 years; height: 173±6 cm; body mass:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The ROM can be used to predict performance in strength sports [40]. Previous studies showed that higher ROM values allow for biomechanical benefits, such as better physical performance through the use of strength for longer periods [41][42][43][44][45] and higher technical quality of movement [7,21,46]. Once an athlete has established the ROM profile of the technical movement, athletes can focus on the next goals, namely, technical efficiency and load mobilisation, which are considered the key elements to optimising athletic performance in weightlifting movements [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The ROM can be used to predict performance in strength sports [40]. Previous studies showed that higher ROM values allow for biomechanical benefits, such as better physical performance through the use of strength for longer periods [41][42][43][44][45] and higher technical quality of movement [7,21,46]. Once an athlete has established the ROM profile of the technical movement, athletes can focus on the next goals, namely, technical efficiency and load mobilisation, which are considered the key elements to optimising athletic performance in weightlifting movements [47,48].…”
Section: Discussionmentioning
confidence: 99%